CLINICO - PATHOLOGICAL CHANGES IN SHEEP EXPERIMENTALLY INFECTED WITH EHRLICHIA RUMINANTIUM (UM BIAGA -ISOLATE) - MOHAMMED, M. S.; HASSAN, S. M; ABDEL RAHMAN, M. B; SHAMAT, A. M; GAMEEL, A. A. (Journal of Veterinary Medicine and Animal Production, 2022)
An experimental infection of sheep with Um Biaga isolate of Ehrlichia ruminantium was made to determine the pathogenisity of the isolate, using in-vitro isolate from Amblyomma. lepidum adults ticks collected from cattle at Um Biaga village (Sennar, State) by inoculating homogenate in adult Nubian goats in January 2003. Seven Desert sheep of Dubassi eco-type purchased from Shendi town known to be a heartwater free area were assigned into two groups. Group I composed of three animals served as uninfected control. Group II composed of four animals that were inoculated intravenously with 5 ml of infected blood from the Nubian goats. The clinical signs and postmortem findings of the infected group were typical of heartwater. The main pathological findings observed were hydropericardium, hydrothorax, lung congestion and oedema of lymph nodes and brain. The histopathological findings showed intensive leukocyte stasis and severe perivascular infiltration in the lung, lymph nodes, myocardium and brain. The convoluted tubules and collecting ducts of kidneys were dilated and Bowman,s spaces were widened. The mean haematological values from the infected sheep indicated that a decrease in PCV, RBCs count and Hb content coincided with fever while a slight increase in WBCs count was observed. Alterations in plasma biochemical parameters were not significant in most of the infected group.